Acoustic emission characteristics of instability process of a rock plate under concentrated loading - S.R. Wang; C.Y. Li; Z.S. Zou; X.L. Liu (Fracture and Structural Integrity)
It can facilitate the understanding of the mechanical properties and failure laws of rocks to research on the rock failure mechanism and evolution characteristics of Acoustic Emission (AE). Under the concentrated loading condition, the fracture and instability test of a rock plate was conducted by using the rock Mechanics Testing System (MTS), meanwhile, these AE events were recorded through the AE recording system. Based on the laboratory test, the numerical simulation was completed by using FLAC3D technique under the criterion that the rupture of a cell or several adjacent cells was regarded as an AE event. The results show that the process of the fracture and instability of the rock plate can be divided into four stages, such as the stress adjusting stage, the brittle fracture stage, the rock-arch bearing load stage and the rock-arch instability stage. And the acoustic emissions display the different characteristics in each one of the four stages. The temporal and spatial distribution characteristics of the AE events with large magnitudes are very similar to those of the natural earthquakes.